Nucleolar protein nucleolin functions in replication stress–induced DNA damage responses. (6th March 2019) - Kawamura, Kasumi; Qi, Fei; Meng, Qingmei; Hayashi, Ikue; Kobayashi, Junya
Abstract: The nucleolus contains multiple copies of ribosomal (r)DNA, which indicate sites of frequent replication stress and suggest the existence of a mechanism to prevent replication stress–related rDNA instability and the possibility that such a mechanism contributes to the whole genomic stability against replication stress. We have previously reported that nucleolin, a major nucleolar protein, is involved in ionizing radiation–induced DNA damage responses (DDRs) such as ataxia telangiectasia mutated (ATM)-dependent cell cycle checkpoints and homologous recombination (HR) repair. Here, we investigated the role of nucleolin in DDR due to replication stress. The results indicate that following replication stress, nucleolin interacted with the histone γH2AX, proliferating cell nuclear antigen (PCNA), and replication protein A (RPA)32, suggesting that it may be recruited to DNA damage sites on the replication fork. Furthermore, the knockdown of nucleolin by siRNA reduced the activation of ATM and RAD3-related (ATR) kinase and the formation of RAD51 and RPA32 foci after replication stress due to UV or camptothecin exposure, whereas nucleolin overexpression augmented ATR-dependent phosphorylation and RAD51 and RPA accumulation on chromatin. Moreover, these overexpressing cells seemed to increase repair activity and resistance to replication stress. Our results indicate that nucleolin plays an important role in replication stress–induced DDRs such as ATR activation and HR repair. Given that nucleolin overexpression is often observed in many types of cancer cells, our findings suggest that nucleolin is involved in the regulation of resistance to replication stress that may otherwise lead to tumorigenesis and it could be a possible target for chemotherapy and radiotherapy.